2021
DOI: 10.21608/ajfm.2021.138590
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Possible Protective Effect of Alpha-Lipoic Acid on Paracetamol induced Oxidative Stress and Hepatic Toxicity in albino rats

Abstract: Background: Paracetamol, is the most widely used over-the-counter analgesic and antipyretic medication in the world, which has minimal adverse effects at therapeutic dosages. But in high doses causes hepatic damage and oxidative stress. Objectives: The current study was designed to investigate paracetamol toxic effects upon the liver and oxidative stress after repeated oral dose and evaluate possible protective effect of alpha lipoic acid when co-administered with and after paracetamol. Methods: forty eight wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The animals treated with AEAASB at doses of 250 and 500 mg/kg and the satellite test group showed normal structural characteristics of the kidneys and liver. This is in agreement with the results of Dhibi et al [ 61 ] and Allam et al [ 62 ] who showed, respectively, that Eucalyptus globulus extract prevented renal alterations and alpha-lipoic acid prevented liver damage induced by paracetamol overdose administration in rats. These results suggest that AEAASB prevented paracetamol-induced damage.…”
Section: Discussionsupporting
confidence: 93%
“…The animals treated with AEAASB at doses of 250 and 500 mg/kg and the satellite test group showed normal structural characteristics of the kidneys and liver. This is in agreement with the results of Dhibi et al [ 61 ] and Allam et al [ 62 ] who showed, respectively, that Eucalyptus globulus extract prevented renal alterations and alpha-lipoic acid prevented liver damage induced by paracetamol overdose administration in rats. These results suggest that AEAASB prevented paracetamol-induced damage.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the results of enzymes (AST, ALT and ALP) were clearly indicated the hepatotoxic effect of the APAP at the dose used since there were a significant increase in all of these hepatic enzymes in APAP group at both periods (14 and 28 days). Elevated liver enzymes (AST, ALT and ALP) in positive control group with liver damage and cell necrosis were also reported in other studies which attributed to the accumulation of APAP toxic metabolite, namely NAPQI in liver tissues causing oxidative stress effects (45). It was reported that a toxic dose of paracetamol leads to the consumption of the stored glutathione (GSH) and sulfate.…”
Section: Discussionmentioning
confidence: 59%